Prenatal diagnosis of fetal isolated right coronary artery to left ventricle fistula. Issue 5 (19th April 2019) - Zhao, Leisheng; Wang, Yu; Wang, Meilian; Sun, Xue; Ma, Jianing; Li, Jingjing; Zhang, Ying
Abstract : Coronary artery fistula (CAF) is a rare malformation and is seldom reported during pregnancy. Right coronary artery fistula commonly drains into the right ventricle, right atrium, or pulmonary artery. We describe here a rare case of fetal CAF draining into the left ventricle using cross‐sectional and color Doppler echocardiography. We also summarized our experience in the diagnosis of this uncommon malformation, in which tracing the origin, course, and outlet of the abnormal intra‐cardiac flow played a key role.